A literature review and new data of trace metals fluxes from worldwide active volcanoes - Calabrese, S.; Scaglione, S.; D'Alessandro, W.; Brusca, L.; Bellomo, S.; Parello, F. (INGV, 2012)
Volcanic emissions are considered one of the major natural sources of several trace metals (e.g. As, Cd, Cu, Pb, and Zn) to the atmosphere [Nriagu, 1989], and the geochemical cycles of these elements have to be considered strongly influenced by volcanic input. However, the accurate estimation of the global volcanic emissions of volatile trace metals into the atmosphere is still affected by a high level of uncertainty. The latter depends on the large variability in the emission of the different volcanoes, and on their changing stage of activity. Moreover, only few of the potential sources in the world have been directly measured [Hinkley et al. 1999]. Atmospheric deposition processes (wet and dry) are the pathways through which volcanic emissions return to the ground (soils, plants, aquifers), resulting in both harmful and beneficial effects [Baxter et al. 1982; Aiuppa et al. 2000; Brusca et al. 2001; Delmelle, 2003; Bellomo et al. 2007; Martin et al. 2009; Floor et al. 2011; Calabrese et al. 2011]. In the first part of this study we present the results of a literature review on trace metals emissions from active volcanoes around the world. In the second part, we present new data on the fluxes of the trace metals from Etna (Italy) and four active volcanoes in the world: Turrialba (Costarica), Nyiragongo (DRC), Mutnovsky and Gorely (Kamchatka). We found 27 publications (the first dating back to the 70’s), 13 of which relate to the Etna and the other include some of the world’s most active volcanoes: Mt. St. Helens, Erebus, Merapi, White Island, Kilauea, Popocatepetl, Galeras, Indonesian arc, Satasuma and Masaya. The review shows that currently there are very few data available, and that the most studied volcano is Mt. Etna. Using these data, we defined a range of fluxes for As, Ba, Bi, Cd, Cu, Fe, Mn, Pb, Se, V and Zn (Figure 1). To obtain new data we sampled particulate filters at the five above mentioned volcanoes. Filters were mineralized (acid digestion) and analyzed by ICP-MS. Sulphur to trace element ratios ...